Cryptocurrencies Bandwagon…Fad wave or Investment Asset? Firm Level Analysis of Panel Data in Egypt - Galal, Yasmine (AUC Knowledge Fountain, 2022)
The crypto market is growing rapidly and gaining momentum globally. The current study is tackling the impact of the crypto exchanges on the stock market in Egypt. The author consolidated firm level data from DataStream and Cryptocurrency data from CoinDesk to conduct this study over the period 2014-2020. The methodology is based on Fixed Effect and IV-GMM models to study the differential impact across sectors and firm attributes. Our main findings can be highlighted as follows: (a) cryptocurrencies are substitutes to stocks. (b)Two periods are highlighted in the analysis: 2016 post currency devaluation and COVID-19 pandemic, where the adoption was found to increase. (c) There was a sectoral differential aspect, where stocks of sectors exhibiting the highest risk and return were more prone to be substituted by crypto assets (for instance IT and Telecom) as opposed to stable and low risk sectors (for instance Pharma and Healthcare). (d) Finally, from an attributes perspective the most impacted firms are new entrants, largest firms, the ones with high debt financing (especially long-term debt) and with high leverage as well as the most profitable ones. This study provides three main contributions to the current literature. First, it extends the literature of the Firm theory by introducing crypto market variables as an essential determinant for the firm stock prices and market value trends. Second, the study highlights the differential impact across sector attributes and firm inherent characteristics. Finally, the results of the study show that cryptocurrency market plays a significant role in investors’ portfolio decisions, even in developing countries like Egypt.